Subtle signs of racial biases among lower secondary teachers in Portugal - R. Costa-Lopes; Mscarenhas, M.; Rodrigues, R. B. (Subtle signs of racial biases among lower secondary teachers in Portugal, 2024)
In Portugal, Black high school students are more than twice as likely as their White counterparts to be directed towards professional education, a pathway that hinders access to higher studies and may place them at a disadvantage. Explanations for inequalities in education outcomes often focus on students’ achievement, family resources, and structural factors, such as place of residence. However, as racially biased perceptions and recommendations by teachers in lower secondary education may also play a role in this phenomenon, the SCOLOR survey was conducted to assess these dimensions among a sample of about 1,000 lower secondary teachers in Portugal. This research study sought to answer the question: “Do teachers make different recommendations depending on whether students are Black or White?”. It also intended to provide an insight on whether teachers’ recommendations and expectations regarding Black and White students’ school pathways may be influenced by their potentially biased perceptions of achievement and behaviour. The results of the survey provide no clear and robust evidence of systematic biases among Portuguese White teachers towards Black students. However, several important exceptions reveal subtle signs of such biases. In particular, the results show that information about performance and behaviour is mobilised in such a way that some recommendations favour White students while others are unfavourable to Black ones. Furthermore, the simple fact that a student was White or Black was enough to prompt different word choices within open-ended questions.